Mengembangkan Keterampilan Berbicara Mahasiswa Semester 3 AMIK Tri Dharma Palu melalui Pengajaran dan Pembelajaran Kontekstual - Vemmy Maidita Nur Aisyiah; Hasan Basri; Sudarkam R. Mertosono; Mawardin M. Said; Aminah Suriaman (Universitas Tadulako, 2023)
The aim of this research is to prove that applying contextual teaching and learning can develop speaking skills of semester 3 Students of AMIK Tri Dharma Palu. The research applied quasi experimental with non-equivalent control group. The population was 95 students of semester 3 of AMIK Tri Dharma Palu. The samples were 42 students selected employing purposive sampling technique. Paper and-pencil method was used when collecting the data with a test as the instrument. The test was administered twice namely pretest and posttest. The data were analyzed statistically using 0.05 level of significance and 40 degree of freedom. The result show that after receiving intervention through contextual teaching and learning, students’ score got improved. In other words, applying contextual teaching and learning is effective in developing students’ speaking skill of semester 3 of AMIK Tri Dharma Palu.